Strength and Hydration Heat of Concrete using Fly Ash as a Partial Replacement of Cement - Sarker, Prabir; McKenzie, Luke (Concrete Institute of Australia, 2009)
The benefits of using fly ash as a partial replacement for cement in concrete are well documented. This paper presents the strength development and hydration heat properties of concrete using Class F fly ash sourced from Western Australia. Compressive strengths at different ages were determined and semi-adiabatic temperature rise during the initial stage of hydration was measured by thermocouples. The 28-day compressive strengths of two control concrete mixtures were 62 and 68 MPa. It was found from the experimental results that the average 28-day compressive strengths of concretes with 30% and 40% cement replacements by fly ash were 84% and 63% of the strengths of the respective control mixtures. However, the 90-day strength of concrete with 30% cement replacement was equal to the strength of the control concrete. A 20% reduction in the maximum temperature was observed in the concrete with 40% cement replacement by the fly ash. It is found from the test data that the percentage reduction in the maximum temperature of fly ash concrete can be estimated as one-half of the percentage replacement of cement by fly ash.